2016
DOI: 10.2106/jbjs.16.00224
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Idiopathic Scoliosis in Adolescents

Abstract: The early detection of idiopathic scoliosis has been advocated since the 1950s and '60s, concurrent with the development in the modern era of ambulatory spinal orthoses to treat scoliosis in adolescents. This led to the development of screening programs for specific populations, as evidenced by school screening programs in the United States and public health systems in Europe and Asia. Over time, the value of population screening in terms of optimal health care and economics has been debated in the popular pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 18 publications
0
49
1
Order By: Relevance
“…However, in a previous study, the BMIs of AIS participants aged 15e17 years were significantly lower than those of the healthy group [17]. Boys reach puberty approximately 2 years after girls at age 13e14 years [33]; therefore, the different outcome observed in this study is thought to be because our population included seventh grade students corresponding to 13-year-old students, i.e., before puberty. In this study, the higher BMI group was shown to have low occurrence of AIS in both sexes.…”
Section: Discussioncontrasting
confidence: 57%
“…However, in a previous study, the BMIs of AIS participants aged 15e17 years were significantly lower than those of the healthy group [17]. Boys reach puberty approximately 2 years after girls at age 13e14 years [33]; therefore, the different outcome observed in this study is thought to be because our population included seventh grade students corresponding to 13-year-old students, i.e., before puberty. In this study, the higher BMI group was shown to have low occurrence of AIS in both sexes.…”
Section: Discussioncontrasting
confidence: 57%
“…The Scoliosis Research Society (SRS) recommends an ATR of 5°to 7°as a threshold for referral for radiography. 1 Cobb angle: Measure, in degrees, of lateral spinal curvature. 2 Requires radiographs for measurement.…”
Section: Screeningmentioning
confidence: 99%
“…The American Academy of Pediatrics, as well as several orthopedic societies, endorse the position of the Scoliosis Research Society that advocates screening examinations for scoliosis to occur at 10 to 12 years of age for females and 13 to 14 years of age for males. 2,4 Similarly Bright Futures recommends spine examination at every well-child encounter to assess for deformity and scoliosis. 24 While obtaining a history, particular attention should be paid to the patient's past medical and surgical history.…”
Section: Diagnosing and Monitoringmentioning
confidence: 99%
“…Modern imaging techniques, as well as careful clinical examination, have revealed that it is also a 3-dimensional deformity including rotation and often results in lordosis at the apex of the curvature. 2 Scoliosis may be postural, also called nonstructural or functional scoliosis; this type is easily manipulated with postural supports or positional cues. However, most scoliosis is structural and is the result of wedgeshaped changes to the affected discs and vertebrae 3 and includes specific types of scoliosis like idiopathic and neuromuscular scoliosis.…”
mentioning
confidence: 99%